Quantifying Marine Debris Pollution in Mangrove Ecosystems: A Study from Kalangan Hamlet, Lampung, Indonesia - Muhamad Gilang Arindra Putra; Muhammad Reza; Rara Diantari; Darma Yuliana; David Julian; Inggar Damayanti; Nur Afni Afrianti (Forest and Nature, 2025)
Mangrove ecosystems are currently facing severe threats due to the accumulation of marine debris, particularly plastic waste. This study aims to quantify the types and weights of marine debris in the mangrove ecosystem of Kalangan Hamlet, Lampung, Indonesia, and analyze their impact on various mangrove species. Data collection was conducted in three zones with different levels of human activity: low, medium, and high. Data on the types and weight of debris were collected using the transect plot method. Correspondence analysis was used to examine the relationship between debris types and the intensity of human activity. The results showed that plastic waste was the most dominant type in terms of both quantity and weight, particularly in areas with moderate to high levels of activity. Over 90% of the waste composition consisted of plastic, weighing over 9,000 g at Stations 2 and 3. Mangrove species of the genus Rhizophora were the most affected, likely due to their complex root structure, which effectively traps waste. Other types of waste, such as fabric, rubber, and glass, were also found in significant quantities and correlated with tourism and community activities. Waste accumulation, particularly plastic, not only alters habitat structure but also hinders mangrove regeneration, which could ultimately reduce ecosystem function and biodiversity. Waste management should align with the area's activity level, with high-activity zones requiring more intensive clean-ups, proper facilities, and regulation enforcement. Community engagement and awareness are crucial in reducing the impacts of marine debris on mangroves. Its temporal scope and sampling frequency limit this study; broader and longer-term research is recommended.